The Mythic Structure of Olga Tokarczuk’s Novel Flights - Skikaitė, Izabelė (Colloquia, 2022)
Olga Tokarczuk’s Flights consists of fragments of different genres which narrate different stories. Although literary scholars have stressed the unusual nature of novel’s structure, the question of what it means remains unanswered. The aim of this article is to reveal the novel’s semantic universe and to examine how the sections that tell different stories relate to each other. The article reveals the system of values, based on the framework of static vs. dynamic, linking the characters in the novel. Using the concept of the modern pilgrimage, the author of the article answers the question of how the opposing values are matched. In accomplishing it, the attention is paid not only to the content but also to the dimension of expression, i.e. how the work is constructed. The conclusion has been drawn that the narrative episodes are linked to the principle of metonymy, i.e. the relationship between the part and the whole, described by Roman Jakobson. In Tokarczuk’s novel, different stories are juxtaposed or contrasted with each other, depending on the recurring inter- and intra-corporeal connections. Lévi-Strauss’s notion of myth allowed the author to observe that the narratives in the novel resemble fragments of myth, and that Flights functions as a contemporary myth, where the structure encodes the issue of man’s relationship to others and themselves and the pain that results from it.